2022
DOI: 10.1128/msphere.00938-21
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus fumigatus ffmA Encodes a C 2 H 2 -Containing Transcriptional Regulator That Modulates Azole Resistance and Is Required for Normal Growth

Abstract: Infections associated with azole-resistant forms of the primary human pathogen Aspergillus fumigatus are associated with poor outcomes in patient populations. This makes analysis of the mechanisms underlying azole resistance of A. fumigatus a high priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“…It is worth to note that mutations in cyp51A gene associated with azole resistance are well known. However, different studies have been recently reported that some other gene loci including ATP-Binding Cassette Transporters ( Cdr1B ) , AtrR, Hmg1, HapE and FfmA are required for wild-type azole resistance in A. fumigatus as the most studied species in Aspergillus genus [ 17 , 18 , 19 , 20 , 21 ]. Likewise, it was suggested that the most common azole resistance allele currently described is a linked change corresponding to a change in the coding sequence of cyp51A and a duplication of a 34-bp region in the promoter leading to a tandem repeat [ 40 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth to note that mutations in cyp51A gene associated with azole resistance are well known. However, different studies have been recently reported that some other gene loci including ATP-Binding Cassette Transporters ( Cdr1B ) , AtrR, Hmg1, HapE and FfmA are required for wild-type azole resistance in A. fumigatus as the most studied species in Aspergillus genus [ 17 , 18 , 19 , 20 , 21 ]. Likewise, it was suggested that the most common azole resistance allele currently described is a linked change corresponding to a change in the coding sequence of cyp51A and a duplication of a 34-bp region in the promoter leading to a tandem repeat [ 40 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In response to triazoles acting on the locus of cyp51A and cyp51B genes, resulting mutation manifests as a non-synonymous substitution that alters the sequence of encoded proteins and thus resistant mutants are aroused [ 15 , 16 ]. However, mutation in non- cyp 51 gene including ATP-binding cassette transporters ( Cdr1B or abcG1 ) , AtrR, Hmg1, HapE and FfmA gene loci have been recently reported [ 17 , 18 , 19 , 20 , 21 ]. In recent years, whole genome sequencing (WGS) and bioinformatics methodologies have gained traction in the diagnostic field as potent appliances for detecting antifungal resistance in medical mycology [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A screen of the library of A. fumigatus transcription factor gene disruptions led to the identification of a C2H2 protein called FfmA as a regulator of azole resistance, in part due to its effect on transcription of the abcG1 gene ( Furukawa et al . 2020 ; Paul, Bowyer, et al . 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…2019 ). An ffmAΔ strain exhibited very low expression of abcG1 , a phenotype that could be suppressed when AtrR was expressed from the strong hspA promoter ( Paul, Bowyer, et al . 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation